dependency of the elite Algerian football on sports channels as a source of information A field study about a sample of footballers and coaches - لموشي , محمد; بن زروق, جمال (sports creativity, 2025)
This study aims to know how much depend of the extent of elite Algerian football on sport channels as a source of information and their reflection of cognitive, behavioral influences. To achieve the ebjectif we use the mass media, we gathered information by using the electronic questionnaire form which 160 persons answered them. these are the results: the extent of the elite football always followed sport channels more than 5 years ago and they choose 3 Arab channels for hour to 3 hours a day .They watched them to have the latest local and global news also venting feeling towards the positive news about their National team and favorite clubs.